Costimulatory Pathways in Kidney Transplantation: Pathogenetic Role, Clinical Significance and New Therapeutic Opportunities. (4th May 2014) - Esposito, Pasquale; Grosjean, Fabrizio; Rampino, Teresa; Libetta, Carmelo; Gregorini, Marilena; Fasoli, Gianluca; Marchi, Gianluca; Sileno, Giuseppe; Montagna, Francesca; Dal Canton, Antonio
<x xml:space="preserve">Abstract</x> Costimulatory pathways play a key role in immunity, providing the second signal required for a full activation of adaptive immune response. Different costimulatory families (CD28, TNF-related, adhesion and TIM molecules), characterized by structural and functional analogies, have been described. Costimulatory molecules modulate T cell activation, B cell function, Ig production, cytokine release and many other processes, including atherosclerosis. Patients suffering from renal diseases present significant alterations of the costimulatory pathways, which might make them particularly liable to infections. These alterations are further pronounced in patients undergoing kidney transplantation. In these patients, different costimulatory patterns have been related to distinct clinical features. The importance that costimulation has gained during the last years has led to development of several pharmacological approaches to modulate this critical step in the immune activation. Different drugs, mainly monoclonal antibodies targeting various costimulatory molecules (i.e. anti-CD80, CTLA-4 fusion proteins, anti-CD154, anti-CD40, etc.) were designed and tested in both experimental and clinical studies. The results of these studies highlighted some criticisms, but also some promising findings and now costimulatory blockade is considered a suitable strategy, with belatacept (a CTLA-4 fusion protein) being approved as the first costimulatory blocker for use in renal transplantation. In this review, we summarize the current knowledge on costimulatory pathways in the setting of kidney transplantation. We describe the principal costimulatory molecule families, their role and clinical significance in patients undergoing renal transplantation and the new therapeutic approaches that have been developed to modulate the costimulatory pathways.